The effect of monocular depth cues on the detection of moving objects by moving observers. (July 2016) - Royden, Constance S.; Parsons, Daniel; Travatello, Joshua
Highlights: Monocular depth cues aid moving observers in detecting moving objects. Adding monocular depth cues decreased thresholds for moving object detection. Depth variation did not cause a large change the thresholds for object detection. Abstract: An observer moving through the world must be able to identify and locate moving objects in the scene. In principle, one could accomplish this task by detecting object images moving at a different angle or speed than the images of other items in the optic flow field. While angle of motion provides an unambiguous cue that an object is moving relative to other items in the scene, a difference in speed could be due to a difference in the depth of the objects and thus is an ambiguous cue. We tested whether the addition of information about the distance of objects from the observer, in the form of monocular depth cues, aided detection of moving objects. We found that thresholds for detection of object motion decreased as we increased the number of depth cues available to the observer.